Role of three dimensional (3D) printing in endourology: An update from EAU young academic urologists (YAU) urolithiasis and endourology working group - Hameed, B. M. Zeeshan; Pietropaolo, Amelia; Naik, Nithesh; Noronha, Calvin; Juliebø-Jones, Patrick; Mykoniatis, Ioannis; Esperto, Francesco; Shah, Milap; Ibrahim, Sufyan; Shetty, Dasharathraj K; Karimi, Hadis; Sharma, Diya; et al. (Frontiers in Surgery, 2022)
The management of nephrolithiasis has been complemented well by modern technological advancements like virtual reality, three-dimensional (3D) printing etc. In this review, we discuss the applications of 3D printing in treating stone disease using percutaneous nephrolithotomy (PCNL) and retrograde intrarenal surgery (RIRS). PCNL surgeries, when preceded by a training phase using a 3D printed model, aid surgeons to choose the proper course of action, which results in better procedural outcomes. The 3D printed models have also been extensively used to train junior residents and novice surgeons to improve their proficiency in the procedure. Such novel measures include different approaches employed to 3D print a model, from 3D printing the entire pelvicalyceal system with the surrounding tissues to 3D printing simple surgical guides.